(untitled) (Alberta Journal of Educational Research, 2012)
This autoethnographic study explores the experiences of two part-time doctoral students as we document our journey of balancing our multiple competing roles. As we reflected and consulted the literature, we began to identify many benefits and challenges that part-time candidature brings to students, universities and employers. Through our autoethnographic analysis, considered in the context of research, we hope to shed light on the part-time doctoral student experience and raise awareness of the benefits that part-time students can bring to universities and to society. Cette étude auto-ethnographique explore les expériences de deux étudiants au doctorat à temps partiel qui documentent leur parcours alors qu’ils tentent d’équilibrer leurs divers rôles concurrents. Au cours de réflexions personnelles et de consultation de la littérature, nous avons commencé à identifier plusieurs avantages et défis que présentent aux étudiants, aux universités et aux employeurs les études doctorales à temps partiel. Nous espérons que cette analyse auto-ethnographique, considérée dans le contexte de la recherche, mettra en lumière l’expérience d’étudiants au doctorat à temps partiel, et fera mieux connaitre les avantages qu’apportent aux universités et à la société les étudiants à temps partiel.